Molecular Evolution and Functional Divergence of Soluble Starch Synthase Genes in Cassava (Manihot Esculenta Crantz). (January 2013) - Yang, Zefeng; Wang, Yifan; Xu, Shuhui; Xu, Chenwu; Yan, Changjie
Soluble starch synthases (SSs) are major enzymes involved in starch biosynthesis in plants. Cassava starch has many remarkable characteristics, which should be influenced by the evolution of SS genes in this starchy root crop. In this work, we performed a comprehensive phylogenetic and evolutionary analysis of the soluble starch synthases in cassava. Genome-wide identification showed that there are 9 genes encoding soluble starch synthases in cassava. All of the soluble starch synthases encoded by these genes contain both Glyco_transf_5 and Glycos_transf_1 domains, and a correlation analysis showed evidence of coevolution between these 2 domains in cassava SS genes. The SS genes in land plants can be divided into 6 subfamilies that were formed before the origin of seed plants, and species-specific expansion has contributed to the evolution of this family in cassava. A functional divergence analysis for this family provided statistical evidence for shifted evolutionary rates between the subfamilies of land plant soluble starch synthases. Although the main selective pressure acting on land plant SS genes was purifying selection, our results also revealed that point mutation with positive selection contributed to the evolution of 2 SS genes in cassava. The remarkable cassava starch characteristics might be the result of both the duplication and adaptive selection of SS genes.